2018
DOI: 10.1111/bph.14198
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar α6‐subunit‐containing GABAA receptors: a novel therapeutic target for disrupted prepulse inhibition in neuropsychiatric disorders

Abstract: Positive allosteric modulation of cerebellar α GABA receptors rescued disrupted PPI by attenuating granule cell activity. α GABA receptor-selective PAMs are potential medicines for treating sensorimotor gating deficits in neuropsychiatric disorders. A mechanistic hypothesis is based on evidence for cerebellar contributions to cognitive functioning including sensorimotor gating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 27 publications
(55 citation statements)
references
References 60 publications
4
51
0
Order By: Relevance
“…The recent demonstration that a6b3g2 receptors not only occur in the cerebellar granule cells, the cochlea nucleus, olfactory bulb, spinal cord, and retina (Gutiérrez et al, 1996) but also in the trigeminal ganglia (Hayasaki et al, 2006), striatum (Leggio et al, 2015) and in the hippocampus (Yang et al, 2016), suggests that PZ-II-029, LAU159, and its congeners might have interesting applications in diseases in which this receptor subtype plays a role. This conclusion is supported by recent reports suggesting that a6-containing GABA A receptors may play a role in neuropsychiatric disorders with sensorimotor gating deficits, such as tic disorders, certain symptoms of schizophrenia, obsessive compulsive disorders, attention deficit disorders, and Huntington's chorea (Liao et al, 2016;Chiou et al, 2018), as well as in depression (Yang et al, 2016), trigeminal orofacial pain (Puri et al, 2012;Kramer and Bellinger, 2013), trigeminal neuropathy, and migraine (PCT/US2016/035761).…”
Section: G Compounds Preferentially Modulating A4bg2 And/or A6bg2 Resupporting
confidence: 67%
“…The recent demonstration that a6b3g2 receptors not only occur in the cerebellar granule cells, the cochlea nucleus, olfactory bulb, spinal cord, and retina (Gutiérrez et al, 1996) but also in the trigeminal ganglia (Hayasaki et al, 2006), striatum (Leggio et al, 2015) and in the hippocampus (Yang et al, 2016), suggests that PZ-II-029, LAU159, and its congeners might have interesting applications in diseases in which this receptor subtype plays a role. This conclusion is supported by recent reports suggesting that a6-containing GABA A receptors may play a role in neuropsychiatric disorders with sensorimotor gating deficits, such as tic disorders, certain symptoms of schizophrenia, obsessive compulsive disorders, attention deficit disorders, and Huntington's chorea (Liao et al, 2016;Chiou et al, 2018), as well as in depression (Yang et al, 2016), trigeminal orofacial pain (Puri et al, 2012;Kramer and Bellinger, 2013), trigeminal neuropathy, and migraine (PCT/US2016/035761).…”
Section: G Compounds Preferentially Modulating A4bg2 And/or A6bg2 Resupporting
confidence: 67%
“…To further substantiate that Compound 6 targets α6GABA A Rs located in TG, we investigated whether systemic administration of a BBB-impermeable α6GABA A R antagonist would block the effects of Compound 6. Furosemide was used since it is BBB-impermeable (Seelig et al, 1994) and it is an α6GABA A R-selective antagonist that effectively blocked the effects of Compound 6, Ro 15–4513 and loreclezole in our previous study (Chiou et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we have identified several pyrazoloquinolinones (Treven et al, 2018; Varagic et al, 2013a; Varagic et al, 2013b) and their deuterated derivatives (Knutson et al, 2018) as PAMs highly selective for GABA A Rs consisting of α6β2/3γ2 subunits, and displayed their lack of sedative, ataxic and cytotoxic effects in rodents (Knutson et al, 2018). Particularly, Compound 6 (originally coded as PZ-II-029) (Chiou et al, 2018; Varagic et al, 2013a; Varagic et al, 2013b; Zhang et al, 1995), a highly selective α6GABA A R PAM, has recently been used to explore the functional role of cerebellar α6GABA A Rs in the regulation of sensorimotor gating in our previous study (Chiou et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, we mostly focused on receptors containing the α6-subunit, which have gained recent attention as potential novel future drug targets. α6-containing GABAA receptors have been reported to contribute to the alleviation of sensorimotor gating deficits (Chiou et al, 2018 ) and orofacial pain and migraine (Fan et al, 2018 ) in animal and cell models. Moreover, models of essential tremor and trigeminal neuropathic pain also have been demonstrated to benefit from drugs that act on α6-containing GABAA receptors (Handforth et al, 2018 ; Vasović et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that α6 subunits are recruited for the strengthening of synapses and added to α1 subunit containing postsynaptic densities (Accardi et al, 2015 ). Recent research has identified a number of putative pathophysiological roles which involve α6-containing receptors, and targeting these is considered an interesting strategy for disorders with sensorimotor gating deficits (Chiou et al, 2018 ), essential tremor (Handforth et al, 2018 ), and by way of receptors thought to be localized in the trigeminal ganglia, trigeminal neuropathic pain states (Puri et al, 2012 ; Vasović et al, 2019 ) and migraine (Fan et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%